Technology-aided open inquiry effects on students' critical and creative thinking skills in physics - Fabello, Javy M.
The purpose of the study was to investigate the effects of Technology-aided Open Inquiry on critical and creative thinking skills of Grade 10 physics students. The study utilized a quasi-experimental two-group pretest-posttest design on two sections of Grade 10 physics students in an all-boys school in Quezon City. One section was exposed to technology-aided open inquiry (TAOI) approach while the other section was exposed to the conventional teaching approach (CTA). Both sections were taught by the teacher-researcher during the last term of academic year 2015-2016. The critical thinking skills of the students were measured using the Watson-Glaser Critical Thinking Appraisal Test (WGCTAT) while the creative thinking skills were measured by the Torrance Test of Creative Thinking (TTCT) Verbal Test A. The gathered data were analyzed using t-test for independent samples, t-test for paired samples, one-way ANCOVA, and linear regression. Based on the findings, it was concluded that: (1) Students exposed to technology-aided open inquiry do not have significantly higher mean posttest score in Watson-Glaser Critical Thinking Appraisal test than those exposed to conventional teaching approach; (2) Students exposed to technology-aided open inquiry have significantly higher mean posttest score in Torrance Test of Creative Thinking than those exposed to conventional teaching approach; and (3) Critical thinking skills do not significantly positively predict creative thinking skills. It is recommended that teachers use the TAOI approach in teaching physics, that school heads provide teacher training and seminar-workshops and procure technology and equipment in support of the TAOI approach; and that future researchers examine the effects of TAOI on other variables like concept understanding, achievement in physics, and ICT skills.